Al-Usus Al-Ta’limiyah Li I’dadi Mawad Ta’lim Al-Lughah Al-’Arabiyah - Shofwatul Fu’adah; Aisyatul Hanun; Maskuri maskuri; Ruwaida Hudatullah; Amirul Mukminin (The Center for Language Development, Mataram State Islamic University., 2023)
Teaching Materials are an important component that must exist in learning, as well as in learning Arabic. Its existence is very helpful in achieving learning objectives. Therefore, the preparation and selection of teaching materials/materials is one of the important things that really must be prepared carefully. The process of compiling teaching materials must be based on principles, foundations or basis for compiling teaching materials, including the basics of education (al-usus al-tarbawiyah). This study discusses what are the principles and foundations of education that must be included in teaching materials, especially Arabic. The method used in this research is literature review. Researchers collect information data through documents, both written documents, and electronic documents about educational principles in the preparation of teaching materials. The educational principles in the preparation of teaching materials are divided into several areas, including the principles of organizing teaching materials, the principles of clarity of educational materials and their legibility, the principles of conformity of teaching materials and the possibility of teaching them. These educational principles are then discussed in detail and systematically as the basis for compiling quality Arabic language teaching materials.